ANALGESIC EFFECTS OF PEPPERMINT ESSENTIAL OIL (MENTHA PIPERITA) IN MUSCLE PAIN AND TENSION-TYPE HEADACHE: A CLINICAL REVIEW (Vietnam Journal of Community Medicine, 2026)
Objectives: To synthesize clinical evidence on the analgesic effects of peppermint essential oil (PEO) for muscle pain and tension-type headache, and to position PEO within current multimodal care.Methods: We searched PubMed, Cochrane, and major publishers (January 2010 to October 2025) using terms related to peppermint oil/menthol, tension-type headache, myalgia, and randomized controlled trials. Inclusion prioritized randomized or controlled studies, systematic reviews, and mechanistic reviews relevant to topical PEO or menthol in humans. Evidence was summarized narratively with emphasis on clinical applicability.Results: For tension-type headache, controlled crossover trials show that 10% peppermint oil in ethanol significantly reduces headache intensity versus placebo within 15-60 minutes; efficacy appears comparable to 1000 mg Paracetamol in acute tension-type headache with favorable tolerability. A later narrative review concludes PEO 10% is licensed for acute tension-type headache in adults and children ≥ 6 years in some jurisdictions and is considered a standard option for acute therapy. For musculoskeletal pain, randomized and controlled studies suggest topical menthol decreases pain associated with delayed-onset muscle soreness and chronic regional pain, with small-to-moderate effects; a 2023 systematic review indicates essential-oil topicals can reduce pain and stiffness when used as add-on therapy. Mechanistically, menthol activates TRPM8 and modulates nociception, supporting counterirritation and cooling analgesia. Adverse effects are uncommon and mild with topical use; ingestion is not recommended.Conclusion: Topical peppermint oil/menthol can provide short-term analgesia for acute tension-type headache and mild-to-moderate muscle pain, particularly as an adjunct to guideline-based care (exercise, education, first-line analgesics). Higher-quality, parameter-standardized RCTs with longer follow-up are warranted to refine indications and dosing.
Keywords: Peppermint essential oil, menthol, tension-type headache, muscle pain, topical analgesic.